Significance of arthrosonography in the diagnosis of metatarsophalangeal joint injury in patients with rheumatoid arthritis - Rita Aleksandrovna Osipyants; D E Karateev; E Yu Panasyuk; G V Lukina; A V Smirnov; S I Glukhova; E N Aleksandrova; A V Volkov (Научно-практическая ревматология, 2013)
Objective: to estimate the contribution of arthrosonography to the diagnosis of metatarsophalangeal joint (MTPJ) injury and to reveal predictors for functional impairments in patients with rheumatoid arthritis (RA). Subjects and methods. The investigation enrolled 50 patients with the RA diagnosis meeting to the American College of Rheumatology 1987 criteria. According to disease duration, the patients were divided into two groups: 1) 9 patients with an early RA history of less than 2 years (ERA); 2) 41 patients with a RA history of over 2 years (LRA). All the patients underwent clinical joint evaluation, laboratory and instrumental examination, including joint X-ray and ultrasonography (USG). Results. An inflammatory process in the foot joints is significantly more frequently detected on ultrasound than clinically (p < 0.0001). The detection rate of erosions, as evidenced by USG, was significantly higher than that by X-ray, in ERA in particular (p = 0.01). Comparison analysis of patients with low and high HAQ scores showed the relationship between functional status, age, pain degree, and inflammatory process in the fifth MTPJ, as shown by USG. There were no associations with disease duration, traditional clinical and laboratory parameters of RA activity, and erosive changes in the feet. Conclusion. Joint USG in daily clinical practice makes it possible to objectively evaluate pathological changes in the feet and the probability of work disability due to RA.